Symbolic Violence in the Organizational Culture of Student Associations at Higher Education in Surabaya - Aza Rifda Khamimiya; Imma Latifa; Anggi Sintya Dewi; Diyah Utami (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2023)
Violent behavior is still often found in the educational environment, including in higher education. The act of violence by seniors against juniors is one example. This violence has become a culture in the campus environment, one of which is in student association organizations, such as symbolic violence. This study aims to identify the causes of symbolic violence and the forms of symbolic violence practices carried out by the management of student association organizations at the state university in Surabaya. The research method used is descriptive-qualitative with an ethnomethodological approach and uses Bordue's theory of symbolic violence. The subjects in this study were members of the 2021 student association organization. This research location is at one of the tertiary institutions in Surabaya. The data collection is done through in-depth interviews. The results indicate differences in vision and mission brought by student association organizations in their implementation, as well as the forms of symbolic violence that occurred in senior orders and threats to juniors, yelling, and scolding. Meanwhile, according to Bourdue himself, the causes of symbolic violence are habitus, capital, and class. In addition, symbolic violence is divided into censorship in the form of marginalization and intimidation and euphemism in the form of generosity, motivation, and obligations. Overall, the research informants were not aware of this practice of symbolic violence, so as a result, it became a culture within the organization. Keywords: symbolic violence, seniority, organization